Stereotactic Body Radiotherapy : A Practical Guide 2026-02-16T12:59:13+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Gaya, Andrew; Mahadevan, Anand (Springer London : Imprint: Springer, 2015)

(untitled)
This practical guide covers the basic  aspects of stereotactic radiotherapy systems and treatment. As an emerging field, stereotactic body radiotherapy (SBRT) offers image-guided radiation that is directed at extremely well-defined tumor targets within the body, delivering very high doses of radiation.  Indications for SBRT have expanded extensively in recent years from intracranial treatment to extracranial, leading to the development of a thriving subspecialty within radiation oncology.   The expertise on these methods is concentrated across a few centres, mainly in the USA. However, as the technique is increasingly being adopted worldwide, specialists require further training in using it. Stereotactic Body Radiotherapy - A Practical Guide provides a valuable aid for this purpose and is of particular interest to clinical oncologists and their trainees